A Posteriori Error Estimates of Triangular Mixed Finite Element Methods for Semilinear Optimal Control Problems (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, we present an a posteriori error estimates of semilinearquadratic constrained optimal control problems using triangular mixed finite elementmethods. The state and co-state are approximated by the order $k≤ 1$ Raviart-Thomas mixed finite element spaces and the control is approximated by piecewiseconstant element. We derive a posteriori error estimates for the coupled state andcontrol approximations. A numerical example is presented in confirmation of thetheory.